Mechanochemically processed Nd−Fe−Co−Cr−B nanoparticles with high coercivity and reduced spin reorientation transition temperature - Chaudhary, Varun (2020)
Nd-Fe-B magnets, possessing the highest energy product, are extensively used in cutting-edge applications, including electrical machines and electrical vehicles. An environmentally benign and cost effective synthesis method of Cr alloyed Nd2 (Fe,Co)14 B magnetic nanoparticles using a dry mechanochemical process is reported. The method is solvent free, facile, energy efficient and scalable. The reduction of mixed oxides of Nd, Fe, Co, B and Cr is performed by using Ca. The coercivity (HC ) of the nanoparticles is found to depend on the dispersant content, with the highest value obtained for Nd2 (Fe11.25 Co2 Cr0.75 )B with 40 % CaO dispersant. The HC of isolated Nd2 (Fe11.25 Co2 Cr0.75 )B nanoparticles and nanoparticles embedded in a CaO matrix is found to be 11.5 kOe and 14.4 kOe, respectively, largest values for heavy rare earth free Nd-Fe-B nanoparticles with reasonable saturation and remanent magnetization, regardless of synthesis route. Considering the density of Nd2 Fe14 B, an energy product of 14.2 MGOe is obtained for the nanoparticles. The thermal coefficient of remanence and thermal coefficient of coercivity for aligned samples are -0.06 % and -0.29 %, respectively, in the temperature range between 100 K and 400 K. The spin reorientation temperature is found to be ∼30 K less than that of bulk Nd2 Fe14 B magnets.